2015
DOI: 10.3354/ame01734
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of quorum sensing autoinducer synthases in the Global Ocean Sampling metagenomic database

Abstract: Quorum sensing (QS) is a cell-to-cell signalling pathway that allows bacteria to synchronize their genetic expression. It is mediated by autoinducers (AI), including (1) acyl-homoserine lactones (AHLs or AI-1), produced by Proteobacteria using AinS, LuxI and HdtS synthase families and (2) furanosyl-diester-borate (FDB or AI-2), produced by a large range of phylogenetically diverse bacteria and synthetized by the LuxS family. Few data have been collected about the presence and importance of QS in marine waters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 70 publications
5
41
1
Order By: Relevance
“…The liberation of dissolved nutrients and organic substrates may benefit surface-associated microorganisms, as well as Trichodesmium bacteria themselves for CO 2 and N 2 fixation, especially in oligotrophic environments. Diverse and novel autoinducer synthase genes have been identified in the Global Ocean Sampling metagenomic database, which covers 68 stations across three oceans (443). Many environmentally important microorganisms, including ammonia-oxidizing, nitrite-oxidizing, anammox, denitrifying, nitrogen-fixing, and sulfur-oxidizing bacteria as well as methanogenic Archaea, employ QS systems (416,435,(444)(445)(446)(447)(448).…”
Section: Microbial Quorum Sensingmentioning
confidence: 99%
“…The liberation of dissolved nutrients and organic substrates may benefit surface-associated microorganisms, as well as Trichodesmium bacteria themselves for CO 2 and N 2 fixation, especially in oligotrophic environments. Diverse and novel autoinducer synthase genes have been identified in the Global Ocean Sampling metagenomic database, which covers 68 stations across three oceans (443). Many environmentally important microorganisms, including ammonia-oxidizing, nitrite-oxidizing, anammox, denitrifying, nitrogen-fixing, and sulfur-oxidizing bacteria as well as methanogenic Archaea, employ QS systems (416,435,(444)(445)(446)(447)(448).…”
Section: Microbial Quorum Sensingmentioning
confidence: 99%
“…For example, Cuadrado-Silva et al (2013) isolated several marine strains with QS systems mediated by different acyl homoserine lactones (AHLs, a class of common QS autoinducers): N-butanoyl homoserine lactone, Nhexanoyl homoserine lactone or both from fouled surfaces. Furthermore, a comprehensive study demonstrated the presence of several autoinducer synthases (responsible for the biosynthesis of different QS autoinducers) in three different oceans, encompassing a large phylogenetic diversity and underpinning its global prevalence (Doberva et al, 2015). The production of AHLs has been described in several marine Gram-negative bacteria (Parsek et al, 1999;Daniels et al, 2004), and the widespread occurrence of QS molecules in marine alphaproteobacteria has been shown for both free-living strains and those associated with eukaryotic algae (Wagner-Döbler et al, 2005).…”
Section: Marine Biofilms and Chemical Cuesmentioning
confidence: 99%
“…Among marine bacteria, AI-2 is only known to function as a signal in Vibrio species (Milton, 2006) and AI-2 producing Vibrio species were found to be predominant and have an important role in microbial communities present in coral reefs or sponges (Tait et al, 2010;Zimmer et al, 2014). There are no much data regarding the presence of AI-2 signals in the ocean beyond coral communities, despite the fact that luxS gene sequences seem to be prevalent in the Global Ocean Sampling database (Doberva et al, 2015). Therefore, it is difficult so far to fully determine the importance of AI-2 in QS of marine bacteria and its role in marine biofilm formation.…”
Section: Marine Biofilms and Chemical Cuesmentioning
confidence: 99%
“…; Doberva et al . ), implying that AI‐2 may be produced by marine micro‐organisms and can play a potential role in microbial‐associated problems (e.g. biofilm formation) prevalent in the seawater application systems.…”
Section: Introductionmentioning
confidence: 99%